Proton vs Hyperarc™ radiosurgery: A planning comparison. Issue 12 (5th November 2020) - Boczkowski, A.; Kelly, P.; Meeks, S. L.; Erhart, K.; Bova, F. J.; Willoughby, T. R.
Abstract: For many patients, stereotactic radiosurgery (SRS) offers a minimally invasive, curative option when surgical techniques are not possible. To date, the literature supporting the efficacy and safety of SRS treatment techniques uses photon beams. However, with the number of proton therapy facilities exponentially growing and the favorable physical properties of proton beam radiation therapy, there is an opportunity to develop proton therapy techniques for SRS. The goal of this paper is to determine the ability of clinical proton treatment planning systems to model small field dosimetry accurately and to compare various planning metrics used to evaluate photon SRS to determine the optimum beam configurations and settings for proton SRS (PSRS) treatment plans. Once established, these plan settings were used to perform a planning comparison on a variety of different SRS cases and compare SRS metrics between the PSRS plans and HyperArc™ (VMAT) SRS plans.